Pleurotus ostreatus spent mushroom compost as green biosorbent for nickel (II) biosorption - Tay, C.C.; Liew, H.H.; Redzwan, Ghufran; Yong, S.K.; Surif, S.; Abdul-Talib, S. (IWA Publishing, 2011)
The potential of Pleurotus ostreatus spent mushroom compost (PSMC) as a green biosorbent for nickel (II) biosorption was investigated in this study. A novel approach of using the half-saturation concentration of biosorbent to rapidly determine the uptake, kinetics and mechanism of biosorption was employed together with cost per unit uptake analysis to determine the potential of this biosorbent. Fifty per cent nickel (II) biosorption was obtained at a half-saturation constant of 0.7 g biosorbent concentration, initial pH in the range of 4–8, 10 min contact time, 50 mL 50 mg/L nickel (II) initial concentration. The experimental data were well fitted with the Langmuir isotherm model and the maximum nickel (II) biosorption was 3.04 mg/g. The results corresponded well to a second pseudo order kinetic model with the coefficient of determination value of 0.9999. Based on FTIR analysis, the general alkyl, hydroxyl or amino, aliphatic alcohol and carbonyl functional groups of biosorbent were involved in the biosorption process. Therefore, biosorption of nickel (II) must involve several mechanisms simultaneously such as physical adsorption, chemisorption and ion exchange. Cost comparison for PSMC with Amberlite IRC-86 ion exchange resin indicates that the biosorbent has the potential to be developed into a cost effective and environmentally friendly treatment system.